2021
DOI: 10.3389/fmicb.2021.771878
|View full text |Cite
|
Sign up to set email alerts
|

Copper Tolerance Mechanism of the Novel Marine Multi-Stress Tolerant Yeast Meyerozyma guilliermondii GXDK6 as Revealed by Integrated Omics Analysis

Abstract: Various agricultural products used in food fermentation are polluted by heavy metals, especially copper, which seriously endangers human health. Methods to remove copper with microbial strategies have gained interests. A novel Meyerozyma guilliermondii GXDK6 could survive independently under high stress of copper (1400 ppm). The copper tolerance mechanism of GXDK6 was revealed by integrated omics in this work. Whole-genome analysis showed that nine genes (i.e., CCC2, CTR3, FRE2, GGT, GST, CAT, SOD2, PXMP4, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…Amino acids metabolic, especially the metabolic of glutathione, cysteine, and methionine, were significantly up-regulated in the treatment of high concentrations of copper, which indicates that these metabolic pathways were responsible for P. spadix ZSY-33 to deal with higher copper stress. These results were consistent with studies in yeast Meyerozyma guilliermondii GXDK6, which reported that the metabolism of glutathione was elevated by the copper stress (Bu et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Amino acids metabolic, especially the metabolic of glutathione, cysteine, and methionine, were significantly up-regulated in the treatment of high concentrations of copper, which indicates that these metabolic pathways were responsible for P. spadix ZSY-33 to deal with higher copper stress. These results were consistent with studies in yeast Meyerozyma guilliermondii GXDK6, which reported that the metabolism of glutathione was elevated by the copper stress (Bu et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Strains from M. guilliermondii have been isolated from a wide variety of environments [59], including deep-sea hydrothermal ridges [60] and dishwashers [61], [62], which are notably known to host extremophilic yeasts [61], [62]. This non-pigmented yeast is known to be tolerant to multiple stresses including salt (16% NaCl [63] and 18% KCl [64]), copper [65] and manganese (5494 ppm) [64]. It has moreover been widely used in biotechnological applications, as it is able to use various substrates for growth and to produce several useful compounds [66].…”
Section: Discussionmentioning
confidence: 99%
“…By MicrobioSee, users can plot a histogram easily with axis transposition and group sorting with one click. The data for this example are from the study of copper tolerance in Meyerozyma guilliermondii GXDK6, which was screened from the mangrove sediments (Bu et al, 2021). Multi-omics techniques were used to explore the tolerance mechanisms of the target strain with different copper ion concentrations.…”
Section: Casementioning
confidence: 99%